STUDY OF PROPERTIES AND DEMOGRAPHY OF CLUMPY GALAXIESBEYOND Z > 3 WITH JWST DATA - Albert Sutanto, Ryo
High redshift star-forming galaxies are known to have different shapes compared to star-forming galaxies in the local universe. These galaxies exhibit irregular shapes and are generally clumpy. These clump features typically have sizes on the kiloparsec scale and possess higher star formation activity compared to the surrounding regions. Clumps are known to form through several mechanisms, such as VDI (Violent Disk Instability) and mergers. This Final Project study aims to analyze 720 spectroscopically identified clumpy galaxies with z > from four JWST observation fields that are also equipped with previous HST observations: CEERS, COSMOS-Web, FRESCO, and PRIMER-UDS. The parameters of these galaxies have been obtained from pre-processed data using the grizli and EAZY pipelines. The detection of clumpy galaxies was conducted automatically using a thresholding segmentation algorithm with PHOTUTILS. Clumpy galaxies were found to have higher stellar mass and star formation rates than non-clumpy galaxies. This facts also supported by the higher fraction of clumpy galaxies at bright MUV values. However, in their star-forming phase, clumpy galaxies do not exhibit active star formation activity but are instead in the main sequence and green valley phases. Over time, the fraction of clumpy galaxies increases from 20% at z = 6 to 60% at z = 3. This study found that the merger rate of clumpy galaxies cannot be explained solely by major mergers but additional scenarios such as minor mergers and VDI are needed. This is also evidenced by the comparison with the trend fit of SFRD (Star Formation Rate Density) correlating with the VDI scenario and major merger rate in the fraction of clumpy galaxies relative to redshift. Clump formation from the VDI and merger scenarios occurs in comparable amounts at z = 3 ? 7, as shown by the clump distance plot. This conclusion reveals there is a transition in clump formation modes from mergers to VDI as redshift decreases or as the universe ages.